From Presence to Popularity: Twitter Use by Members of the Indonesian House of Representatives (2014–2019) in Non-Electoral Setting - Salvatore Simarmata (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2026)
Social media has changed the way politicians communicate and interact with citizens, but research on Indonesian political use of social media in a non-electoral context is still limited. This study aims to fill the gap by examining how members of Indonesia’s legislature (DPR) of the 2014-2019 period adopted and used Twitter (now X) to enhance their online presence, branding, and popularity during non-electoral context. By using political branding theory and the equalization-normalization debate, the study seeks to answer three questions: (1) who among DPR members adopted Twitter, (2) how they used its features for branding and communication, and (3) what factors explain their online popularity. Based on a dataset of 436 Twitter-registered politicians (78% of total 560 DPR members) supplemented by social network analysis, this study finds that online legislators are predominantly male (82%), middle-aged (mean = 51, SD = 9), and university educated. Branding is mostly limited to displaying a profile picture, with small percentage of showing position and party affiliation. Popularity is highly skewed. Education and party size are strong predictors of adoption, and frequency of twitting is an indication of popularity. While large parties like PDIP and Golkar have the most members online, smaller parties such as PKS and NasDem outperform them in proportional Twitter presence. The study gives a contribution to digital political communication scholarship by establishing a baseline of Twitter adoption among legislators in emerging democracy before the current era of online disinformation.